How traditional Norwegian outdoor activities are changing; a 10-year follow up in relation to sociodemographic factors - Stenqvist, Thomas Birkedal; Bere, Elling (Frontiers in Sports and Active Living, 2024)
The study aims to evaluate the relationship between sociodemographic factors and changes in Norwegian outdoor activities between 2008 and 2018. Traditional outdoor activities, such as family trips in nature, the gathering of mushrooms and wild berries, and growing one's own plants to eat, are believed to have a positive impact on physical activity levels and health in general.This study includes repeated cross-sectional surveys conducted in 38 randomly selected schools across two Norwegian counties. In 2008, 1012 parents of 6th and 7th grade students from 27 schools completed a questionnaire. In 2018, 609 new parents from 25 schools participated. Variables were dichotomized. Descriptive analyses between groups were conducted using chi-square statistics. Binary logistic regression analyses were performed with the three outdoor activities as dependent variables, including year only (model 1), and then also gender, age (continuous), education (own and partners), and household income as independent variables (model 2).Results: Participation in weekly family trips in nature increased from 22% to 28% (p=0.002), the OR for year 2018 vs. year 2008 was 1.51. Adjusted for sociodemographic factors, the OR remained stable and significant. Education was the only significant sociodemographic factor (OR=1.60), indicating the odds of those with a higher education to be 60% higher to engage in weekly family trips in nature. Gathering of wild mushrooms and plants remained stable with time. Being female (OR=1.44), age (OR=1.049) and education (OR=1.49) was related to gathering. An increase in growing plants to eat was observed with an increase from 42% to 51% (p<0.001), OR=1.33. However, it did not remain significant in model 2. Education was, in general, positively related to growing food (OR=1.35).We observed a positive increase in family trips in nature over the period from 2008 to 2018. Furthermore, elder parents seem to be more involved in the long-rooted traditional Norwegian grow-and gather culture, and a social gradient is apparent as those with higher education do participate more often in traditional outdoor activities.